2014
DOI: 10.3349/ymj.2014.55.2.476
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Vitamin D Is Associated with Anti-Thyroid Peroxidase Antibody in Autoimmune Thyroiditis

Abstract: PurposeThe association between autoimmune thyroid diseases (AITDs) and vitamin D deficiency is controversial. We aimed to evaluate the relationship between serum 25-hydroxy-vitamin D3 [25(OH)D3] and anti-thyroid antibody levels.Materials and Methods25(OH)D3, anti-thyroid antibodies, and thyroid function measured in 304 patients who visited the endocrinology clinic were analyzed. The patients were subgrouped into the AITDs or non-AITDs category according to the presence or absence of anti-thyroid antibodies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 28 publications
(33 reference statements)
9
83
0
2
Order By: Relevance
“…Distinct from these studies we excluded the subclinical hypothyroidism patients whose ages were not higher than 70 years. In another study, Shin et al (2014) demonstrated a negative association between 25-OH D and anti-TPO levels, and also indicated that the low 25-OH D level was a possible risk factor of anti-TPO positivity.…”
Section: Discussionmentioning
confidence: 88%
“…Distinct from these studies we excluded the subclinical hypothyroidism patients whose ages were not higher than 70 years. In another study, Shin et al (2014) demonstrated a negative association between 25-OH D and anti-TPO levels, and also indicated that the low 25-OH D level was a possible risk factor of anti-TPO positivity.…”
Section: Discussionmentioning
confidence: 88%
“…9 In human studies on the association of vitamin D levels with antithyroid antibodies, lower 25(OH)D levels were found in subjects with higher levels of antithyroid antibodies compared with those who were negative for thyroid autoimmunity. 10 Vitamin D deficiency has been diagnosed more frequently in AITD subjects, especially in those affected by Hashimoto's thyroiditis, than in healthy subjects. 11 In female patients with newly onset GD, a significant relationship of low levels of 25(OH)D with increased thyroid volume was observed, suggesting that vitamin D status may be involved in the pathogenesis of the disease.…”
Section: Vitamin D and Thyroid Autoimmune Diseasementioning
confidence: 99%
“…The role of vitamin D as an immune modulator has been recently emphasized [20]. A recent study conducted in Korea found that patients with elevated antithyroid antibodies had lower levels of serum 25(OH)D3 than those without such elevations [21]. A study conducted in 2011 showed that the prevalence of vitamin D deficiency was significantly higher in patients with autoimmune thyroid diseases than in healthy individuals (72% vs.…”
Section: Associated Disease Frequency Percentagementioning
confidence: 99%